Pengaruh Edukasi Gagal Ginjal Berbasis Booklet Terhadap Score Kesadaran Bahaya Gagal Ginjal (Score Kidney/Kidney Fealure Awwernes) Pada Remaja di Desa Sungai Pasir Tahun 2025 : Penelitian - Yora Nopriani; Ani Rafikah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Booklets are one of the informational media designed to enhance individuals’ understanding of health issues in a self-directed and continuous manner. This study aims to determine the effect of kidney failure education using booklets on the awareness score of kidney failure dangers among adolescents in Sungai Pasir Village in 2025. This research employs a quantitative approach with a pre-experimental design, specifically a one-group pre-test - post-tests design. The sampling technique used was total sampling, with a total of 50 respondents. The research instrument used was the Kidney Disease Patient Awareness Questionnaire. Data analysis was conducted using the Paired Sample t-Test. The results showed that prior to receiving the booklet, most adolescents had a low level of awareness. After the educational intervention, the majority of respondents demonstrated a significant improvement in awareness, reaching a good category. Statistical tests indicated a significant effect of education using booklets on adolescents’ awareness scores regarding the dangers of kidney failure (p-value < 0.05). Based on these findings, it is expected that adolescents will utilize educational booklets as an easily understood source of information to increase their awareness of the dangers of kidney failure.